Identification of Diverse Bat Alphacoronaviruses and Betacoronaviruses in China Provides New Insights Into the Evolution and Origin of Coronavirus-Related Diseases - Han, Yelin; Du, Jiang; Su, Haoxiang; Zhang, Junpeng; Zhu, Guangjian; Zhang, Shuyi; Wu, Zhiqiang; Jin, Qi (Frontiers in Microbiology, 2019)
Outbreaks of severe acute respiratory syndrome (SARS) in 2002, Middle East respiratory syndrome in 2012 and fatal swine acute diarrhea syndrome in 2017 caused serious infectious diseases in humans and in livestock, resulting in serious public health threats and huge economic losses. All such coronaviruses (CoVs) were confirmed to originate from bats. To continuously monitor the epidemic-related CoVs in bats, virome analysis was used to classify CoVs from 831 bats of 15 species in Yunnan, Guangxi, and Sichuan Provinces between August 2016 and May 2017. We identified 11 CoV strains from 22 individual samples of four bat species. Identification of four alpha-CoVs from Scotophilus kuhlii in Guangxi, which was closely related to a previously reported bat CoV and porcine epidemic diarrhea virus (PEDV), revealed a bat-swine lineage under the genus Alphacoronavirus. A recombinant CoV showed that the PEDV probably originated from the CoV of S. kuhlii. Another alpha-CoV, α-YN2018, from Rhinolophus affinis in Yunnan, suggested that this alpha-CoV lineage had multiple host origins, and α-YN2018 had recombined with CoVs of other bat species over time. We identified five SARS-related CoVs (SARSr-CoVs) in Rhinolophus bats from Sichuan and Yunnan and confirmed that angiotensin-converting enzyme 2 usable SARSr-CoVs were continuously circulating in Rhinolophus spp. in Yunnan. The other beta-CoV, strain β-GX2018, found in Cynopterus sphinx of Guangxi, represented an independently evolved lineage different from known CoVs of Rousettus and Eonycteris bats. The identification of diverse CoVs here provides new genetic data for understanding the distribution and source of pathogenic CoVs in China.